PDE3 inhibitor and EGCG combination treatment suppress cancer stem cell properties in pancreatic ductal adenocarcinoma - Motofumi Kumazoe (Nature Portfolio, 2017)
Abstract Recurrence following chemotherapy is observed in the majority of patients with pancreatic ductal adenocarcinoma (PDAC). Recent studies suggest that cancer stem cells (CSCs) may be involved in PDAC recurrence and metastasis. However, an efficient approach to targeting pancreatic CSCs remains to be established. Here we show that in cancer cells overexpressing the 67-kDa laminin receptor (67LR)-dependent cyclic GMP (cGMP) inducer, epigallocatechin-3-O-gallate (EGCG) and a phosphodiesterase 3 (PDE3) inhibitor in combination significantly suppressed the Forkhead box O3 and CD44 axis, which is indispensable for the CSC properties of PDAC. We confirmed that the EGCG and PDE3 inhibitor in combination strongly suppressed tumour formation and liver metastasis in vivo. We also found that a synthesized EGCG analog capable of inducing strong cGMP production drastically suppressed the CSC properties of PDAC and extended the survival period in vivo. In conclusion, the combination treatment of EGCG and a PDE3 inhibitor as a strong cGMP inducer could be a potential treatment candidate for the eradication of CSCs of PDAC.